Croatia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews economic developments in the Republic of Croatia during 1990-95. Real gross domestic product fell by a cumulative 30 percent over 1991-93. However, the economy began to recover in 1994 and real GDP grew by 0.8 percent. In the first quarter of 1995, real GDP was nearly 1 percent higher than the corresponding quarter in 1994. The primary impetus to growth in 1994 was from tourism, trade, transport, and communication. Tourism grew by 15 percent in 1994.